2020
DOI: 10.3390/app10092997
|View full text |Cite
|
Sign up to set email alerts
|

Selected Antioxidants in Organic vs. Conventionally Grown Apple Fruits

Abstract: The apple (Malus domestica Borkh.) is one of the most widely cultivated temperate fruits globally, gaining scientific interest as a rich source of antioxidants with a demonstrated beneficial human health impact. Since a growing number of consumers are increasingly seeking safe and healthy food options, alternative fruit production systems such as organic farming, and their potential to provide safe and nutritious foods, have been gaining increasing attention in the last decades. The aim of the presented study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…To summarize, the phenolic compounds in the apple fruits showed cultivar-specific responses to fruit bagging treatment, and the content of phenolic compounds was also affected by the number of days of re-exposure to the sunlight before harvest. Previous research has suggested that organic farming may increase the content of phenolic compounds in apple fruits [51]. The findings of the current study and previous research highlight the importance of cultivation practices, together with that of genetic background and environment, as factors influencing the composition and quality of apple fruits.…”
Section: Effect Of Bagging On Phenolic Compounds Compositionsupporting
confidence: 72%
“…To summarize, the phenolic compounds in the apple fruits showed cultivar-specific responses to fruit bagging treatment, and the content of phenolic compounds was also affected by the number of days of re-exposure to the sunlight before harvest. Previous research has suggested that organic farming may increase the content of phenolic compounds in apple fruits [51]. The findings of the current study and previous research highlight the importance of cultivation practices, together with that of genetic background and environment, as factors influencing the composition and quality of apple fruits.…”
Section: Effect Of Bagging On Phenolic Compounds Compositionsupporting
confidence: 72%
“…Fertilization affected the biosynthesis of phenolic acids; organic raspberries showed ~9%, ~30%, and ~40% higher concentration of phenolic acids at the pink, ripe and overripe stage when compared to conventional raspberries ( p ≤ 0.05). Sedrnicka-Tober et al [ 50 ] found 31% higher concentration of phenolic acids in organic apples when compared to conventional apples in the three different apple varieties studied. The lowest phenolic acid concentration was observed in conventional raspberries at the overripe stage (~56 mg/100 g dry weight), while the highest phenolic acid concentration was observed at the same ripe stage in organic fruits (77 mg/100 g dry weight), ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, because some functional food consumers may be skeptical of the capacity of efficient meals to deliver on the promise of health benefits, the functional food manufacturing industry has focused on the development of certified functional foods (CFFs) [ 7 ]. Given that an increasing number of people are seeking safe and healthy food alternatives [ 8 ], the market for CFFs is growing worldwide [ 9 ].…”
Section: Introductionmentioning
confidence: 99%